2016
DOI: 10.1371/journal.pone.0161731
|View full text |Cite
|
Sign up to set email alerts
|

The 29.5 kb APOBEC3B Deletion Polymorphism Is Not Associated with Clinical Outcome of Breast Cancer

Abstract: Increased APOBEC3B mRNA levels are associated with a hypermutator phenotype and poor prognosis in ER-positive breast cancer patients. In addition, a 29.5 kb deletion polymorphism of APOBEC3B, resulting in an APOBEC3A-B hybrid transcript, has been associated with an increased breast cancer risk and the hypermutator phenotype. Here we evaluated whether the APOBEC3B deletion polymorphism also associates with clinical outcome of breast cancer. Copy number analysis was performed by quantitative PCR (qPCR) in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…DNA extracts from an earlier retrospective study (21) were selected from our bio-bank at the Erasmus MC ( Supplementary Fig. S1).…”
Section: Study Cohort and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA extracts from an earlier retrospective study (21) were selected from our bio-bank at the Erasmus MC ( Supplementary Fig. S1).…”
Section: Study Cohort and Samplingmentioning
confidence: 99%
“…22). Followup and tumor response were defined based on the criteria by the International Union Against Cancer (23) and the European Organization for Research and Treatment of Cancer (24) as described previously (21). Estrogen receptor (ER) status, progesterone receptor (PR) status, and ERBB2 (HER2) amplification were determined as described before (25,26,27).…”
Section: Study Cohort and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…A3H Hap I was identified to induce genomic mutations specifically in lung cancer 13 . Interestingly, the activity of A3H Hap I was found because researchers wanted to investigate how genomic mutations with a cytidine deaminase signature were still occurring in people with an A3B-/-deletion [51][52][53][54] , which occurs in the world population at 22.5%, although it primarily occurs in Oceanic populations 44 . Although A3A is also involved in cancer mutagenesis, it appears to be strongly associated with breast cancer 31,55 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our expression results are generally inline with the results of Starrett et al [ 64 ] who, also using artificial model (CRISPR/Cas9 generated deletion), showed high expression of APOBEC3B and very low but similar expression of APOBEC3A and APOBEC3A/APOBEC3B. The previous studies of the APOBEC3B deletion genotype-expression relationship (i) did not distinguish the canonical APOBEC3A and the hybrid APOBEC3A/APOBEC3B transcripts, and/or (ii) were conducted using artificially created cell line models with transfected reporter constructs, and/or (iii) were performed with the use of single tissue or cell line samples, and/or (iv) were often inconclusive, at least partially due to high homology between APOBEC3A and APOBEC3B , as well as other members of the APOBEC3 gene family [ 32 , 33 , 40 , 63 , 64 , 73 , 78 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%